Representation of Anxiety in the Poster “قتال” on the Al Qassam Website: A Semiotic Analysis by Roland Barthes - Mahrotul Fithonah; Muassomah (Universitas Negeri Semarang, 2025)
The current events in Gaza, Palestine, are genocides that have claimed many lives. This triggered protests in various parts of the world. Various visual elements appeared, including the circulation of pro-Palestinian posters during the action. The poster is not only an ordinary publication medium, but it also conveys the anxiety of the Palestinian people and serves as a medium of emotional expression that reflects the community's feelings. This study analyzes the visual meaning, particularly in the symbols that represent the concept of anxiety, as depicted in the